Synthesis and characterization of polyaniline-carboxylated PVC composites: Application in development of ammonia sensor - Singh V.; Mohan S.; Singh G.; Pandey P.C.; Prakash R. (My University, 2025)
Polyaniline (PAni) and carboxylated polyvinyl chloride (PVC) composites were synthesized and studied for their structural, electrical and electrochemical properties and used as a novel material for development of an ammonia gas sensor. Processible conducting composites were prepared by introducing carboxylated PVC in the PAni matrix under vigorous stirring and sonication conditions. Self-standing films of these electroactive and homogeneous composites were obtained by a solution casting method. A significant improvement in processibility, stability and mechanical property was observed in the composite films having PAni up to 90 wt% of total content. However, the electrical conductivity decreased remarkably as the percentage of PAni decreased in the composites. An optimum composition of the composite having 80 wt% of PAni was used for development of a conductometric sensor for ammonia. A simple and low cost sensor device based on two-probe conductivity measurement was developed for ammonia gas. The sensor device having two parallel Pt wires separated nearly 100 μm was bridged with a PAni-carboxylated PVC composite film by a dip coating method. Ammonia gas was sensed in a closed glass chamber. The sensor was fast enough to detect ammonia gas down to 1 ppm and was reproducible, as the response was recorded after 5 min and 10 min exposure. © 2008 Elsevier B.V. All rights reserved.